Inflation threshold and the effects on economic growth - ÖZDEMİR YAZGAN, SELİN DEVRİM (BILGESEL YAYINCILIK SAN & TIC LTD, 2012)
Inflation threshold and the effects on economic growth In this paper non-linear relationship between inflation role and economic growth in the period 2003:01-2009:12 and the effects of economic crisis on this relation for Turkey are investigated. At the first stage, according to the results of nonlinearity test procedure, inflation threshold value has been detected and inflation-growth relation has been examined using a two-regime TAR model. According to these, the first finding of this study is that, under the first regime which is below the threshold level, low inflation has significantly positive impact on economic growth. On the other hand, under the second regime which is above the threshold level, high inflation has a significant negative effect on economic growth. The second finding of this study, by examining the effect of 2007 global economic crisis, is that the economic crisis only changes the inflation threshold value. This finding shows that rising inflation is an important obstacle to economic growth due to negative effect. Due to global economic crises and their impacts on inflation and growth, the Central Bank of the Republic of Turkey should follow a determined strategy to eliminate inflation. Besides, the results of the study emphasize that politicians and decision makers must take into account such relations between inflation and growth, too.
Keywords: Turkey; Inflation; Economic Growth; Regime Switching; TAR; Inflation Threshold Value; LONG-RUN GROWTH; EMPIRICAL-ANALYSIS; SPECIFICATION; MODELS